Nanoparticles for Enhanced Oil Recovery Processes - Nwidee, Lezorgia Nekabari (Curtin University, 2017)
With the continuous rise in energy demand and decline in conventional reserves, the oil industries are constantly in search of inventive and novel approaches to optimize hydrocarbon recovery potentials, despite, several decades of deployment of conventional strategies and enhanced methodologies. This study systematically investigates the possibilities of nanostructured materials, specifically nanoparticles, to be of substantial benefit to enhanced oil recovery with a focus on wettability alteration. By investigating the interfacial behaviour of NiO and ZrO2 nanoparticles at solid-liquid interfaces, the study identified a prime characteristic of nanoparticle in EOR, which is its ability to improve the property of the dispersal, even at very low particle concentrations in suspensions, and its capacity to alter hydrophobic limestone reservoir rock surfaces towards hydrophilicity, which is crucial for a variety of EOR related processes - better spontaneous oil displacement, enhanced carbon geo-sequestration and soil-decontamination processes.